Design, microwave‐assisted synthesis, biological evaluation and molecular modeling studies of 4‐phenylthiazoles as potent fatty acid amide hydrolase inhibitors. (5th March 2020) - Wilt, Stephanie R.; Rodriguez, Mark; Le, Thanh N. H.; Baltodano, Emily V.; Salas, Adrian; Pecic, Stevan
Abstract: Endocannabinoids, anandamide (AEA) and 2‐arachidonoylglycerol (2‐AG), are endogenous lipids that activate cannabinoid receptors. Activation of these receptors produces anti‐inflammatory and analgesic effects. Fatty acid amide hydrolase (FAAH) is a membrane enzyme that hydrolases endocannabinoids; thus, inhibition of FAAH represents an attractive approach to develop new therapeutics for treating inflammation and pain. Previously, potent rat FAAH inhibitors containing 2‐naphthyl‐ and 4‐phenylthiazole scaffolds were identified, but up to the present time, very little structure–activity relationship studies have been performed on these moieties. We designed and synthesized several analogs containing these structural motifs and evaluated their inhibition potencies against human FAAH enzyme. In addition, we built and validated a homology model of human FAAH enzyme and performed docking experiments. We identified several inhibitors in the low nanomolar range and calculated their ADME predicted values. These FAAH inhibitors represent promising drug candidates for future preclinical in vivo studies. Abstract : Several 4‐phenylthiazole compounds were synthesized using microwave, and we evaluated their inhibitory potency against human fatty acid amide hydrolase enzyme. Structure–activity relationship study reviled several structural requirements for this series of inhibitors. We confirmed these findings by utilizing homology modeling and docking experiments. Their ADME properties were predicted.